Breathing life into the boring billion: Direct constraints from 1.4 Ga fluid inclusions reveal a fair climate and oxygenated atmosphere - Justin G. Park; Michael Naylor Hudgins; Philip Fralick; Jacob T. Shelley; Morgan F. Schaller (Proceedings of the National Academy of Sciences, 2025)
The Mesoproterozoic eon [1.8 to 0.8 billion years ago (Ga)] is a crucial but enigmatic period in Earth’s history. Many facets of this interval remain unresolved, especially how atmospheric evolution influenced and responded to changes in climate and biology. For example, low atmospheric O 2 concentrations are thought to have inhibited the emergence of animals until the Neoproterozoic. Yet, some p O 2 estimates indicate that the critical threshold for animal respiration was exceeded several hundred million years prior. Likewise, low p CO 2 estimates imply glacial climates should prevail. However, this prediction is inconsistent with an apparent billion-year hiatus in glaciation. We test these hypotheses with direct constraints on the Mesoproterozoic atmosphere from analyses of primary fluid inclusions in 1.4 Ga surficial halite, which reveal an atmospheric p O 2 of 7.84 ± 3.05 mbar and a p CO 2 of 2.76 ± 1.66 mbar. We couple these measurements with average inclusion homogenization temperatures of 31.2 ± 7.8 °C. Our results point to an Earth system state characterized by a moderate climate with sufficient O 2 for early animal respiration. These observations reflect a coevolution of life, climate, and the atmosphere, where a largely unrecognized episode of oxygenation and CO 2 drawdown was driven by the breakup of the supercontinent Nuna and the complexification of algal eukaryotes.